Prostaglandin EP2 receptor signalling inhibits the expression of matrix metalloproteinase 13 in human osteoarthritic chondrocytes. Issue 1 (24th September 2010) - Sato, Tomoo; Konomi, Koji; Fujii, Ryoji; Aono, Hiroyuki; Aratani, Satoko; Yagishita, Naoko; Araya, Natsumi; Yudoh, Kazuo; Beppu, Moroe; Yamano, Yoshihisa; Nishioka, Kusuki; Nakajima, Toshihiro
Abstract : Objectives: Matrix metalloproteinase (MMP) 13 is a pathogenic collagenase that causes cartilage destruction and plays a leading role in causing osteoarthritis. This study focused on 114 genes that are differentially expressed between intact and damaged osteoarthritis cartilage, in order to determine which molecules are involved in suppressing MMP-13 expression. Methods: MMP-13 concentrations were measured in the supernatant of human osteoarthritis chondrocyte cultures transfected with small interfering RNA (siRNA) against the 114 genes. MMP-13 levels changed most dramatically in response to siRNA against prostaglandin EP2 receptor. The authors performed further measurements of MMP-13 production in osteoarthritis chondrocytes stimulated by the EP2 agonist butaprost in the presence or absence of interleukin-1β (IL-1β) and/or cyclooxygenase-2 (COX-2) inhibitor. They also assessed the effect of butaprost on chondrocyte viability, and investigated the involvement of the cAMP–protein kinase A (PKA) pathway on EP2 signalling using inhibitors. Cartilage-related gene expression was examined in chondrocytes treated with butaprost. The authors also investigated which E series of prostaglandin (EP) receptors are expressed in osteoarthritis cartilage. Results: MMP-13 messenger RNA expression was significantly affected by two molecules, EP2 receptor and SLC14A1, a urea transporter. In IL-1β-treated osteoarthritis chondrocytes, butaprost suppressed MMP-13 production, which was further decreased by COX-2 inhibitor. EP2 signalling downregulated MMP-13 mRNA expression via the cAMP–PKA pathway without affecting cell viability. Although EP2 signalling enhanced IL-6 expression, the expressions of several catabolic factors (MMP-1, MMP-3, MMP-13, ADAMTS5, IL-1β and tumour necrosis factor alpha) were inhibited. EP2 receptor was the major EP receptor in osteoarthritis cartilage. Conclusion: The results suggest that EP2 signalling has 'anti-catabolic' effects in osteoarthritis chondrocytes.